Vascular stiffness in children born after frozen or fresh embryo transfer. A cardiac magnetic resonance imaging study of 8 to 9 year old children. (14th October 2021) - Mizrak, I; Asserhoej, L L; Lund, M A V; Greisen, G; Clausen, T D; Main, K M; Jensen, R B; Vejlstrup, N G; Madsen, P L; Pinborg, A B; ,
Abstract: Background: Vascular stiffness increases during childhood, and increased vascular stiffness is associated with symptomatic cardiovascular disease in adults with metabolic syndrome. In comparison with naturally conceived children (NC), children conceived after in-vitro fertilization by frozen (FET) or fresh embryo transfer (Fresh ET) are at risk of being large- and small-for-gestational-age, respectively. Epigenetic modulation during assisted reproductive technologies (ART) is suggested to influence cardiovascular risk factors, and recent literature suggests that children conceived after ART are at increased risk of insulin resistance, endothelial dysfunction and arterial hypertension. Such changes may be associated with increased vascular stiffness, but it is not yet been examined directly. Purpose: We investigated if ART children are at increased risk of aortic distensibility and pulse-wave velocity. Methods: 150 children aged 8–9 years conceived after FET (n=50), Fresh ET (n=50) or by natural conception (NC, n=50) were studied with magnetic resonance imaging. Conductance artery stiffness was determined from aortic distensibility and aortic pulse-wave velocity (PWV). Data were analyzed with blinding according to treatment group. Based on a conservative estimate for the common SD for the difference between groups of 1.5 mm 2 /mmHg, 36 children were required in each group to detect a difference in aortic distensibility of 10%, which corresponds to a 5 year age difference, with an alpha of 0.05 (double-sided) and a beta of 0.80. We aimed for 50 children in each group to allow for dropouts and non-analyzable scans, and to allow for further determinations. The effects of potential confounders on the effect of conception method on ascending aorta distensibility and total aortic PWV were tested stepwise in four linear regression models (Figure 1). Results: Child groups were comparable with respect to anthropometric measures (Table 1). No differences were observed in systolic or diastolic blood pressure, cardiac output, total peripheral resistance, or in aortic distensibility (Ascending aorta distensibility: FET, ascending aorta 11.12±3.55 10–3 mm 2 /mmHg; Fresh ET 11.77±2.97 10–3 mm 2 /mmHg; NC 11.43±2.82 10–3 mm 2 /mmHg) (ANOVA-p=0.58) or aortic PWV (PWV of total aorta: FET, 3.69±0.75 m/s; Fresh ET, 3.49±0.31 m/s; NC, 3.59±0.61 m/s) (ANOVA-p=0.26). The effect of ART remained non-significant after adjustment for child sex, maternal BMI at early pregnancy, and maternal educational level (Figure 1). Conclusion: The effects of ART on aortic distensibility were not statistically significant, but in the direction of the hypothesis of stiffer conductance arteries from frozen embryo transfer. The confidence interval was relatively wide, and the results suggest that the difference between frozen and fresh embryo transfer may in fact correspond to an age difference of more than 5 years. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Novo Nordisk Foundation